Chronic nicotine effects on left ventricular function in healthy middle‐aged people: an echocardiographic study. (25th February 2013) - Sundström, D.; Waldenborg, M.; Magnuson, A.; Emilsson, K.
Summary Aims Cigarettes and Swedish snuff influence the cardiovascular system in many ways. Cigarette and snuff usage have been linked with an acute impairment in several diastolic cardiac parameters during intake. The aim of this study is to investigate whether long‐term usage of Swedish snuff or cigarettes also causes a more permanent impairment of systolic and/or diastolic cardiac parameters in the left ventricle in otherwise healthy middle‐aged snuffers and smokers. Methods and results Eighty‐seven age‐matched volunteers were included and examined with echocardiography. The volunteers were divided into three subgroups; one group with non‐tobacco users, one group with long‐term smokers and finally one group with long‐term snuffers. The smokers and snuffers were instructed not to use these products for at least 5 h before the examination. The systolic and diastolic cardiac parameters were collected at one time. Most of the systolic parameters measured were unaltered between the tobacco subgroups and non‐tobacco users, and therefore, no alteration of significance was found in systolic parameters. Also, almost all of the diastolic parameters measured were not significantly impaired in the tobacco subgroups compared with non‐tobacco users. However, the deceleration time (DT) was slightly prolonged (P<0·05) and thus statistically significant in the tobacco subgroups. This finding is somewhat difficult to interpret but may be seen as random. Conclusions This study reveals that most systolic‐ and diastolic cardiac parameters are not chronically significantly altered in middle‐aged long‐term tobacco users compared with age‐matched non‐tobacco users.